Greater one-horned rhino (Rhinoceros unicornis) behaviour during high floods at Kaziranga National Park and the Burhachapori Wildlife Sanctuary, Assam, India - Deba Kumar Dutta; Pranab Jyoti Bora; Rabin Sharma; Anupam Sarmah; Amit Sharma; Jitendra Kumar; KS Dekaraja; Rohini B Saikia; Andrew Halliday (Pachyderm)
The behaviour of the greater one-horned rhinoceros (Rhinoceros unicornis) (GOH) in response to exposure to natural hazards like floods is poorly understood. This study recorded the behaviour of GOH in highland refuges during periods of seasonal and extreme flooding in two protected areas in the Brahmaputra River valley (Assam, India): Kaziranga National Park (KNP) and Burhachapori Wildlife Sanctuary (BWS). Following the death after monsoon floods in 2016 of a lone sub-adult female translocated to BWS from KNP, the study compared the behaviour of this individual during high flood periods to that of other adults, sub-adults and calves in KNP in 2017. Adult rhinos of KNP spent most of the time resting during high flood periods, which may be a behavioural response to overcome stress. By contrast, both calves and sub-adult rhinos in KNP and especially the lone BWS sub-adult female rhino were observed swimming from one highland to another, despite the heavy floodwater current. Sub-adults in KNP dedicated considerable time to feeding; however, the sub-adult in BWS spent less time feeding than any of the age groups in KNP, and her weakened state from starvation may have contributed to her death after the floods receded. The study concludes by offering recommendations to help rhinos survive and recover from seasonal flooding. Adult animals may be the better choice for future rhino translocations from KNP to other flood plain habitats than subadult rhinos or a mother with calf.